2002
DOI: 10.1111/j.1572-0241.2002.05847.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of misoprostol on ibuprofen-induced renal dysfunction in patients with decompensated cirrhosis: results of a double-blind placebo-controlled parallel group study

Abstract: Ibuprofen causes renal dysfunction in decompensated cirrhotics, whereas misoprostol may have some protective renal effects, which are, however, short lived and clinically insignificant. Because of side effects, misoprostol should be used with caution in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…The study suggested that the risk of developing this complication in cirrhotic patients using NSAIDs are approximately three times more than cirrhotic patients who do not use these compounds ( 40 ). The renal impairment with reduced glomerular filtration rate (GFR), renal blood flow, and sodium and water excretion has been indicated in cirrhotic patients when different NSAIDs including ibuprofen ( 41 , 42 ), indomethacin ( 43 ) aspirin ( 44 ) naproxen ( 45 ) and sulindac are administered ( 46 ).…”
Section: Resultsmentioning
confidence: 99%
“…The study suggested that the risk of developing this complication in cirrhotic patients using NSAIDs are approximately three times more than cirrhotic patients who do not use these compounds ( 40 ). The renal impairment with reduced glomerular filtration rate (GFR), renal blood flow, and sodium and water excretion has been indicated in cirrhotic patients when different NSAIDs including ibuprofen ( 41 , 42 ), indomethacin ( 43 ) aspirin ( 44 ) naproxen ( 45 ) and sulindac are administered ( 46 ).…”
Section: Resultsmentioning
confidence: 99%
“… 477 Indeed, roughly 10% of total drug-induced hepatotoxicity cases are related to NSAIDs, 478 and NSAID-induced liver injury is well documents. 466 , 479 Moreover, NSAIDs can cause nephrotoxicity, 480 gastric ulcer, hemorrhage, 481 , 482 decompensation of liver function, etc. 472 …”
Section: Drug Treatment For Cancer Pain In Hccmentioning
confidence: 99%
“…Indeed, roughly 10% of total drug-induced hepatotoxicity cases are related to NSAIDs ( 478 ), and NSAID-induced liver injury is well documents ( 466 , 479 ). Moreover, NSAIDs can cause nephrotoxicity ( 480 ), gastric ulcer, hemorrhage ( 481 , 482 ), decompensation of liver function, etc. ( 472 ).…”
Section: Drug Treatment For Cancer Pain In Hccmentioning
confidence: 99%